Influencia de la emisión de neutrones en la medición por el método de la doble energía de la distribución de masa y energía cinética de los fragmentos de la fisión espontánea del 252Cf - Montoya y Cols., Modesto (2019)
The double energy method has been used by several authors to measure the mass (A *) and total kinetic energy (EKT *) distribution of the complementary fragments from spontaneous fission of 252Cf, finding an broadening of the distribution standard deviation EKT * (σEKT *) in the region near mass symmetry (A * = 226). Using Monte Carlo method, we show that this broadening is because for each value of A * an overlapping of distributions EKT * for primary fragments with two or more neighboring masses, respectively, are produced.